G Protein–Coupled Receptor Kinase 5 Gene Polymorphisms Are Associated With Postoperative Atrial Fibrillation After Coronary Artery Bypass Grafting in Patients Receiving β-Blockers - Kertai, Miklos D.; Li, Yen-Wei; Li, Yi-Ju; Shah, Svati H.; Kraus, William E.; Fontes, Manuel L.; Stafford-Smith, Mark; Newman, Mark F.; Podgoreanu, Mihai V.; Mathew, Joseph P. (Circulation. Cardiovascular genetics, 2014)
BACKGROUND—We hypothesized that genetic variations in the adrenergic signaling pathway and cytochrome P450 2D6 enzyme are associated with new-onset atrial fibrillation (AF) in patients who underwent coronary artery bypass grafting and were treated with perioperative β-blockers (BBs). METHODS AND RESULTS—Two cohorts of patients who underwent coronary artery bypass grafting and received perioperative BBs at Duke University Medical Center were studied. In a discovery cohort of 563 individuals from the Perioperative Genetics and Safety Outcomes Study (PEGASUS), using a covariate-adjusted logistic regression analysis, we tested 492 single-nucleotide polymorphisms (SNPs) in 10 candidate genes of the adrenergic signaling pathway and cytochrome P450 2D6 for association with postoperative AF despite perioperative BB therapy. SNPs meeting a false discovery rate ≤0.20 (P<0.002) were then tested in the replication cohort of 245 individuals from the Catheterization Genetics biorepository. Of the 492 SNPs examined, 4 intronic SNPs of the G protein–coupled kinase 5 (GRK5) gene were significantly associated with postoperative AF despite perioperative BB therapy in the discovery cohort with additive odds ratios between 1.72 and 2.75 (P=4.78×10 to 0.0015). Three of these SNPs met nominal significance levels in the replication cohort with odds ratios between 2.07 and 2.60 (P=0.007 to 0.016). However, meta-analysis of the 2 data sets cohorts suggested strong association with postoperative AF despite perioperative BB therapy in all 4 SNPs (meta-P values from 1.66×10 to 3.39×10). CONCLUSIONS—In patients undergoing coronary artery bypass grafting, genetic variation in GRK5 is associated with postoperative AF despite perioperative BB therapy.